FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT (Studi Empiris Pada KAP di Semarang) - Adelita Cassandra Devi, 13.05.62.0030 (Students' Journal of Accounting and Banking, 2016)
This study aimed to examine the effect of independence, work experience, objectivity ,accountability, motivation, and professionalism which directly influence acceptance of audit quality. The population in this study were all auditors working in the public accountant from Semarang. Sampling was done using convenience sampling method and sample size were 71 respondents. The primary data collection method used was a questionnaire method. Data were analyzed using multiple linier regression model. Result of research indicate that the variables: independention, work experience, objectivity, accountability, motivation, proffesionalism significant positive effect to acceptance of audit quality. Keywords :independence, work experience, objectivity ,accountability, motivation, and professionalism which directly influence acceptance of audit quality.